Lebanese adolescents' expectations about social inclusion of peers in intergroup contexts. (15th March 2021) - Hitti, Aline; Melki, Jad; Sahakian, Tina; Killen, Melanie
Abstract : This study examined the role of group norms, group identity, age, contact, and stereotypes on youths' decisions to include a peer in an intergroup context portraying Lebanese and American adolescents. Lebanese participants ( N = 275), ages 12 and 16 years, were surveyed about expectations for inclusion of an out‐group target with similar interests or an in‐group target with different interests into their own Lebanese group or another American group. Findings indicated participants focused on shared interests, rather than national identity, when making inclusion decisions for either group and group norms mattered. Older participants expected American peers to be less inclusive towards an out‐group peer. Direct contact predicted inclusivity of out‐group American peers into one's own Lebanese group, and indirect media‐based contact predicted expectations for inclusivity into an American out‐group. Findings have implications for interventions aimed at improving cross‐national friendships which, in turn, have the potential to reduce prejudicial attitudes.